Evidence for the Existence of an Aerobic Pathway for Synthesis of Monounsaturated Fatty Acids by Alcaligenes faecalis - Ghaneker, A. S. (1973)
Studies on the composition of total fatty acids of Alcaligenes faecalis harvested at different growth phases have been carried out. Ability of the organism to desaturate palmitic and stearic acid has also been tested. The organism contained palmitic (16:0), stearic (18:0), palmitoleic (16:1), cis-vaccenic (18:1), cyclopropane (17:▽ and 19:▽), and three hydroxy acids. Increase in cyclopropane acids and corresponding decrease in monounsaturated acids in direct proportion to the age of the culture were observed, whereas other fatty acids remained relatively unaltered. A growing culture of the organism was found to desaturate [1-(14)C]palmitic acid supplied in the medium to hexadecanoic acid. Resting cells desaturated [1-(14)C]palmitic and [1-(14)C]stearic acid giving rise to about 50% of (14)C in the COOH group of corresponding monounsaturated fatty acids.